CCENT Cisco certified entry networking technician - Lammle, Todd (Serious skills., 2008)
"Start your preparation for Cisco's new CCENT entry-level networking certification, your entry point into Cisco's popular CCNA certification track. This comprehensive study guide from leading Cisco authority Todd Lammle thoroughly prepares you for the Interconnecting Cisco Networking Devices, Part 1 exam (640-822) and the start of a career, with pages of exam essentials, real-world scenarios, and hands-on exercises. Topics include the operation of data networks, how to implement both switched and routed networks, and much more"--Resource description page.